Overview of Psychoactive Substance Use Among Medical Students - Fatimah, Firda; Eliezer, Victor; Kusdiyah, Erny (Scientific Of Environmental Health and Diseases, 2025)
Background: Psychoactive substance abuse is a global health problem with physical, psychological, and social impacts. Final-year students are a vulnerable group to psychoactive substance use due to academic demands, stress, and environmental factors. However, research on the profile of psychoactive substance use among medical students is still limited, particularly at the University of Jambi. Research Objective: To determine the profile of psychoactive substance use among students preparing their thesis proposals in the Medical Study Program at the University of Jambi in 2025. Methods: This study used a descriptive design with a qualitative approach and was conducted from February to May 2025 at the Faculty of Medicine and Medicine, UNJA. A sample of 139 students was determined using the Slovin formula. The research instrument used the Indonesian version of the WHO-ASSIST questionnaire and was analyzed univariately to obtain the frequency distribution of psychoactive substance use. Results: Of the total person, 20 had used psychoactive substances in their lifetime, with the most common types of substances being cigarettes, alcohol, inhalants, and sedatives/sleeping pills. Use in the past 3 months was found in 14 individuals, predominantly cigarettes and alcohol. Three individuals reported receiving attention from others regarding their substance use habits, and three had unsuccessfully attempted to quit. No intravenous drug use was found. The most common substances used were cigarettes (14 individuals) and alcohol (8 individuals). Conclusion: Final-year medical students at the University of Jambi were found to have a history of psychoactive substance use, with the highest prevalence being cigarettes and alcohol. These results indicate the need for education and interventions to prevent psychoactive substance abuse in academic settings.